Enemy Construction in the Declaration of War against Japanese Empire: CDA Perspective (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
This paper seeks to identify and describe the linguistic priming work that President Roosevelt employed in overcoming isolationism in the United States. In his Declaration of War against the Japanese Empire, President Roosevelt asked the American people to trust him with the American forces and American determination using the strategy of enemy construction. Making courageous statements packed in political discourse, he framed the people's minds into a state of patriotic country defenders and that the Japanese Empire was an enemy and a real danger to the life of the country. His statements are a formulation that America is ready for war with an assurance of a near-absolute victory. Applying the method and theories of Critical Discourse Analysis centered around the framework of